2015
DOI: 10.1371/journal.pone.0120895
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Modulate Migration and Invasion of Human Tongue Squamous Cell Carcinoma

Abstract: Oral tongue squamous cell carcinoma (OTSCC) has a high mortality rate and the incidence is rising worldwide. Despite advances in treatment, the disease lacks specific prognostic markers and treatment modality. The spreading of OTSCC is dependent on the tumor microenvironment and involves tumor-associated macrophages (TAMs). Although the presence of TAMs is associated with poor prognosis in OTSCC, the specific mechanisms underlying this are still unknown. The aim here was to investigate the effect of macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 64 publications
1
39
0
Order By: Relevance
“…Even though these SASP factors, such as CCL5/RANTES [37, 38], were able to significantly stimulate cSCC cell migration (Supplementary Figure S3), they were produced at even higher levels by SCC cells themselves in an autocrine manner, as have been previously reported [39, 40]. Therefore, any significant paracrine contribution from senescent dermal fibroblasts was ruled out.…”
Section: Resultsmentioning
confidence: 79%
“…Even though these SASP factors, such as CCL5/RANTES [37, 38], were able to significantly stimulate cSCC cell migration (Supplementary Figure S3), they were produced at even higher levels by SCC cells themselves in an autocrine manner, as have been previously reported [39, 40]. Therefore, any significant paracrine contribution from senescent dermal fibroblasts was ruled out.…”
Section: Resultsmentioning
confidence: 79%
“…In addition, CD68+ TAMs, commonly identified by the expression of CD163, CD206, or CD204, also sustain the development and progression of many tumors, including oropharyngeal cancer, by suppressing the cytotoxic activity of CD8+ T cells, and promoting angiogenesis and tumor cell migration …”
Section: Introductionmentioning
confidence: 99%
“…24 In addition, CD68+ TAMs, commonly identified by the expression of CD163, CD206, or CD204, 25 also sustain the development and progression of many tumors, including oropharyngeal cancer, by suppressing the cytotoxic activity of CD8+ T cells, and promoting angiogenesis and tumor cell migration. [26][27][28] In this retrospective study, we aim to obtain a comprehensive "immune signature" of the HPV-negative and HPVpositive OPSCCs using immunohistochemistry (IHC) and immunofluorescence (IF) techniques for HLA expression, the presence of innate and adaptive immune cells and explore their correlation with clinical outcome. Ultimately, with the implementation of univariate and multivariate analysis, we aim to find independent prognostic factors for DFS and DSS of OPSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence indicate that immune cells in the tumor microenvironment play an important role in regulating tumor progression, which may determine the clinical parameters and prognosis [2,3,4,5,6]. Macrophages have been implicated as key contributors to the tumor-microenvironment dynamics [7].…”
Section: Introductionmentioning
confidence: 99%
“…They also play an important role in tumor cell migration and metastasis [9]. Several reports have suggested that TAMs are associated with tumor growth, disease progression, and poor prognosis in some human cancers [2,10].…”
Section: Introductionmentioning
confidence: 99%